LEUKOCYTES DIFFERENTIATION OF Pangasius hypophthalmus WHICH INFECTED BY Aeromonas hydrophilaAND TREATED WITHRhizophora sp. - Chandra Chandra; Henni Syawal; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Rhizophora sp. is one of the mangrove plant which potentially for antibacterial compound, because it has an alkaloids, saponins, flavonoids and tannins. This research purpose was to know the proper dose of Rhizophora sp. leaves extract in healing the MAS disease (Motile Aeromonas Septicaemia), which can be seen through the leukocytes differentiation of Pangasius hypophthalmus. The method in this research was the experimental method using the Completely Randomized Design (CRD) with one factor, four treatment levels and three times replication. The treatments were P0 (without immersion)and the immersion with leaves extract at dose P1 (1300 ppm), dose P2 (1600 ppm), and dose P3 (1900 ppm). The immersion was implemented twice in 24 hours for about 5 minutes. The fishes were used at 13-15 cm of length for 120 fishes which were infected by leaves extract. The results showed that the immersion of Rhizophora sp.leaves extract at dose 1600 ppm of leaves extract dose could treat the MAS disease (Motile Aeromonas Septicaemia) of Pangasius hypophthalmus. The total average of leukocytes was 69,61×103cell/mm3, leukocytes differentiation was 81,33% of lymphocytes, 9,66% of neutrophils, 9,00% of monocytes. The fagocyte index was 36,66% and the survival rate was 84,61%.Key Words : Leukocytes, Pangasius hypophthalmus,Rhizhopora sp.leaves extract